La tecnología en el desarrollo cognitivo en niños y niñas de 4 a 5 años de educación inicial en la unidad educativa “Verbo Divino”, provincia Bolívar, cantón Guaranda, período 2023 – 2024 - Calero Alarcón, Rosa Stefania (2024)
The research project on technology in cognitive development in boys and girls aged 4 to 5 years of Initial Education in the "Verbo Divino" Educational Unit, Bolívar Province, Guaranda Canton, period 2023 - 2024, addresses several topics on technology in children and the use they give to technological devices to improve educational education through academic programs. As its objective is to identify the use of technology in cognitive development in boys and girls aged 4 to 5 years of Initial Education II in the "Divine Verb" Educational Unit, making known the problem that we were able to observe within the classroom, The project has to facilitate the adequate development of behavior, attention and retention by creating technological educational activities related to the topics that are planned and in this way motivate all children in teaching and learning. In order to determine the problem, research techniques were applied to collect information from parents, teachers and children, in this way we can analyze what impact the children have after having worked in a new way in classes, we observe the gestures, emotions and behavior in each of them. The topic of this research arouses the interest of both children, parents and teachers, so they know several technological educational activities that help in the education of children and promote cognitive development in each of them, making classroom classes more fun, motivating that awaken interest in learning.